G545(P) An apparent case of non-accidental injury. (May 2019) - Tan, GH; Bhattacharyya, R
Abstract : A four year old girl of mixed Costa Rican and Chinese origin was admitted to KK Women's and Children's Hospital, Singapore for concerns of non-accidental injury (NAI). She presented with spontaneous bruising with occasional gum bleeding over a period of one month. Parents are divorced and they have joint custody of this child. There was no family history of bleeding tendencies. Examination revealed a girl with multiple bruises and petechiae over the upper and lower limbs. There was no hepatosplenomegaly or significant lymphadenopathies. For the workup, her initial full blood count: Haemoglobin 12.1 g/DL, Total white blood cell count 14.72 × 10*9/L (neutrophil 38%, lymphocyte 29%, monocyte 3%, eosinophil 28%), Platelets 135 × 10*9/L. Her coagulation profile was unremarkable. In view of eosinophilia, she was referred to the Haematology team. Her platelet function test was performed and showed decreased aggregation with ADP, Arach acid, collagen and epinephrine, normal aggregation with ristocetin. A clinical diagnosis of Acquired Platelet Dysfunction with Eosinophilia (APDE) was made. She was discharged home as she was clinically well with no further bleeding tendencies. Parents were reassured of the spontaneous recovery expected with this condition. She was subsequently reviewed in the Haematology outpatient clinic periodically and at her latest visit, her full blood count reflected normalisation of her eosinophil counts. Concurrently, there were no concerns from the police and medical social worker investigations, with regards to child safety and future placement. This case highlights the need for high index of suspicion in children who present with spontaneous bruises.